Improving management of type 1 diabetes in the UK: the Dose Adjustment For Normal Eating (DAFNE) programme as a research test-bed. A mixed-method analysis of the barriers to and facilitators of successful diabetes self-management, a health economic analysis, a cluster randomised controlled trial of different models of delivery of an educational intervention and the potential of insulin pumps and additional educator input to improve outcomes - Simon Heller; Julia Lawton; Stephanie Amiel; Debbie Cooke; Peter Mansell; Alan Brennan; Jackie Elliott; Jonathan Boote; Celia Emery; Wendy Baird; Hasan Basarir; Susan Beveridge; et al. (NIHR Journals Library, 2014)
Background: Many adults with type 1 diabetes cannot self-manage their diabetes effectively and die prematurely with diabetic complications as a result of poor glucose control. Following the positive results obtained from a randomised controlled trial (RCT) by the Dose Adjustment For Normal Eating (DAFNE) group, published in 2002, structured training is recommended for all adults with type 1 diabetes in the UK. Aim: With evidence that blood glucose control is not always improved or sustained, we sought to determine factors explaining why some patients benefit from training more than other patients, identifying barriers to successful self-management, while developing other models to make skills training more accessible and effective. Findings: We confirmed that glycaemic outcomes are not always improved or sustained when the DAFNE programme is delivered routinely, although improvements in psychosocial outcomes are maintained. DAFNE courses and follow-up support is needed to help participants instil and habituate key self-management practices such as regular diary/record keeping. DAFNE graduates need structured professional support following training. This is currently either unavailable or provided ad hoc without a supporting evidence base. Demographic and psychosocial characteristics had minimal explanatory power in predicting glycaemic control but good explanatory power in predicting diabetes-specific quality of life over the following year. We developed a DAFNE course delivered for 1 day per week over 5 weeks. There were no major differences in outcomes between this and a standard 1-week DAFNE course; in both arms of a RCT, glycaemic control improved by less than in the original DAFNE trial. We piloted a course delivering both the DAFNE programme and pump training. The pilot demonstrated the feasibility of a full multicentre RCT and resulted in us obtaining subsequent Health Technology Assessment programme funding. In collaboration with the National Institute for Health Research (NIHR) Diabetes Research Programme at King's College Hospital (RG-PG-0606-1142), London, an intervention for patients with hypoglycaemic problems, DAFNE HART (Dose Adjustment for Normal Eating Hypoglycaemia Awareness Restoration Training), improved impaired hypoglycaemia awareness and is worthy of a formal trial. The health economic work developed a new type 1 diabetes model and confirmed that the DAFNE programme is cost-effective compared with no structured education; indeed, it is cost-saving in the majority of our analyses despite limited glycated haemoglobin benefit. Users made important contributions but this could have been maximised by involving them with grant writing, delaying training until the group was established and funding users' time off work to maximise attendance. Collecting routine clinical data to conduct continuing evaluated roll-out is possible but to do this effectively requires additional administrator support and/or routine electronic data capture. Conclusions: We propose that, in future work, we should modify the current DAFNE curricula to incorporate emerging understanding of behaviour change principles to instil and habituate key self-management behaviours that include key DAFNE competencies. An assessment of numeracy, critical for insulin dose adjustment, may help to determine whether or not additional input/support is required both before and after training. Models of structured support involving professionals should be developed and evaluated, incorporating technological interventions to help overcome the barriers identified above and enable participants to build effective self-management behaviours into their everyday lives. Trial registration: ClinicalTrials.gov NCT01069393. Funding: The NIHR Programme Grants for Applied Research programme.